Heavy Electricals India Ltd. Bhopal A Review of Programming - Planning Commission (Planning Commission, Government of India, 1964)
The review of programming and reporting systems at the Bhopal unit of Heavy Electricals (India) Ltd. (HEL), conducted by the Management Division of the Committee on Plan Projects under the guidance of the Planning Commission, examines the adequacy of management planning, coordination, and control mechanisms within a rapidly expanding public sector undertaking. Initiated to address concerns that project assumptions were frequently delayed, inadequately implemented, or exceeded in cost due to insufficiently detailed planning and weak performance reporting, the study evaluates HEL’s production, financial, and materials management systems and proposes comprehensive reforms. The report characterizes HEL’s challenges as “growing pains” arising from accelerated expansion targets—from an originally envisaged annual output of Rs. 12.5 crores to revised goals of Rs. 33.65 crores and eventually Rs. 50 crores—necessitated by national electrification and industrial development needs. It recommends the establishment of integrated long-term production planning, standardized cost and time parameters, improved budgeting and pricing policies, streamlined financial reporting, and strengthened inventory and materials control systems supported by scientific stock management and mechanized data processing. Additionally, it emphasizes better coordination across departments, enhanced procurement and inspection procedures, and systematic disposal of surplus materials. By situating HEL’s evolution within India’s broader post-independence industrial strategy and public sector expansion, the report underscores the necessity of modern management techniques to achieve higher operational efficiency, financial discipline, and sustained industrial growth in alignment with national development objectives.
Management Group Committee on Plan Projects Planning Commission November
Keywords: Heavy Electricals (India) Ltd.; Bhopal Unit; Committee on Plan Projects; Planning Commission; Production Programming; Financial Programming; Materials Management; Public Sector Undertakings; Integrated Planning System; Cost Control; Inventory Management; Industrial Expansion